A systematic literature review on QoS-aware service composition and selection in cloud environment. (15th May 2018) - Hayyolalam, Vahideh; Pourhaji Kazem, Ali Asghar
Abstract: Generally, cloud computing consists of providing virtualized and scalable resources as services through the Internet dynamically. According to the costumers' requests, various types of services which have the same functionality with different non-functionality features, are delivered in the cloud environment that often should be combined to satisfy the customer's complex requests. Recently, the composition of unique and loosely-coupled services into a preferred system is a prevalent industrial method and a commonly tracked research topic in academia. Service composition deals with generating new value-added services by merging some single existing services to provide an optimal composite service which includes formerly existing single and simple services aims to improve Quality of service (QoS). To the best of our knowledge, in spite of this issue's significance in cloud computing, there is not any comprehensive and systematic single research about this issue with a particular focus on QoS, which takes all metrics inspected in this paper into consideration. The most notable and impact of this paper is that it does not eliminate any paper in this scope, also it investigates more criteria than the current surveys. Hence, the purpose of this paper is to investigate the former mechanisms and techniques in terms of numerous factors. So, it adopts a systematic literature review, vital questions which can be enhanced by the research accomplished to address the stated problem have been extracted and raised. Afterwards, by classifying the researches into two primary groups (centralized and distributed) based on the environment of the problem and identifying the inspected QoS parameters, predefined goals, and developing environments, appropriate outcomes and statistics are attained that can contribute to upcoming works. In other words, this paper focuses to systematically categorize and evaluate the current research approaches and strategies on QoS-aware cloud service composition (published up to August 2017).